Hubungan Antara Komunikasi Dalam Keluarga Dan CitraTubuh Dengan Kecemasan Berbicara Di Depan Umum Pada Mahasiswa Tahun Pertama - Claudia, Novia; Anshori, Muhammad Afif; Ulpa, Eska Prawisudawati; Maharani, Laila (Universitas Islam Negeri Raden Intan Lampung, 2022)
Public speaking is an unpleasant situation accompanied by feelings of fear, worry, and discomfort that will make a person feel unable to convey his message properly and correctly in front of a crowd. This study aims to determine the relationship between k omunikasi d alam k eluarga and citra tubuh with kecemasan berbicara d i depan umum. The population in the study was 80 students of the Mathematics Education Study Program class of 2021, Raden Intan State Islamic University, Lampung. The method in this study is quantitative with cluster sampling technique. The data collection technique used a public speaking anxiety scale of 34 aitems (ɑ = 0.892) a family communication scale of 30 aitems (ɑ = 0.826) and a body image scale of 40 aitems (ɑ = 0.876). The analyst technique used is multiple regression analysis with Sofware JASP version 0.15. The results of the first study showed that there was a significant relationship between communication in the family and body image with anxiety about speaking in front of youmum in first-year students with a value of R = 0.420 and a value of F = 8.269 with a significant degree of p < 0.01 (p <0.01). Secondly, there was a significant negative relationship between communication in the family and public speaking anxiety in first-year students with a grade (Rₓ₁-y) = -0.353 with a significant level p = 0.001 (p < 0.01) with an effective contribution (SE) of 5%. Third, there was a significant negative relationship between body image and public speaking anxiety in first-year students with a grade (Rₓ₁-y) = -0.325 with a significant level p = 0.003 (p < 0.01) with an effective contribution (SE) of 10%. Keywords: Public Speaking Anxiety, Communication In The Family, Body Image.